Characterization of the Ichthyological Population of Hydrosystèmes in the Lagoon Area of the Azagny National Park (Ivory Coast) - Touplé Koné, Sibiri; Kamelan, Marius Tanoh; Raphaël Etile, N’doua; Yao Konan, Aristide; Kouamelan, Paul Esséchti (European Scientific Journal, ESJ, 2021)
The conservation of protected areas is nowadays one of the concerns of international and national institutions. This study aims to contribute to better conservation of the ichthyological fauna of the lagoon area of the Azagny National Park (PNA). This national park has been dealing with the harmful effects of human activities for years. Thus, from March 2019 to February 2020, sampling campaigns were carried out to characterize this space, for better conservation. The results obtained are based on the analysis of abiotic and biotic (fish) data collected at 6 stations. The physicochemical parameters were measured using a multiparameter and the fish population collected using 10 gillnet batteries of 10, 25, 30, 35, 40 and 50 mm mesh void. The analysis of the ichthyological population of the lagoon area reveals a diversity of 53 species belonging to 30 families and 12 orders. 11 species were newly collected while 31 species previously recorded in these hydrosystems were not captured in the present study. The Shannon (H’> 2) and Equitability (E> 0.5) indices calculated reflect a good organization and stability of the ichthyological population of the hydrosystems of the PNA lagoon zone. The Monte-Carlo test indicates that the variables rate of nitrate, width, rate of dissolved oxygen, water temperature, alkalinity, salinity, rate of dissolved solid and phosphorus are those which discriminate specific richness, abundance and the distribution of the stand.